The Application of Marl Clay in Thai Craftmanship - Charoensup, arunee; Jangsuwan, Nungrutai; Chayawat, Jirawun (Journal for Developing the Social and Community, 2020)
The developed marl clay applied as material in Thai craftmanship creativity. Thai style molding pattern using marl clay was utilize as material effectively. The texture of marl clay could rolled or shaped into sculptures and sharp molding pattern with no crack while the work piece dried in a short period without baking. In this research, there were 14 Thai style molding patterns using marl clay; (1) Krachang, (2) Krachang Jerm, (3) Krachang Ta Oi, (4) Krachang Bpa Dhi Yaan, (5) Krachang Bpa Dhi Yaan Ruan, (6) Gleep Bua, (7) Gleep Ka Nun, (8) Dok Loi, (9) Prahmyam, (10) Naa Gra Daan, (11) Dok Seek Dok Son, (12) Down, (13) Ga Nok, (14) Sat Himmaphan. All of 14 Thai style-molding patterns applied to decorate Buddhist scriptures, lotus flower shaped pedestal, table mirror, betel box, and morable pavilion with pointed roof. The result of assessment in all 3 elements (design, production process, utilization) from experts are in highest ranking (table mirror = 4.68 ± 0.55, Buddhist scriptures = 4.60 ± 0.57 and lotus flower shaped pedestal = 4.60 ± 0.55, morable pavilion with pointed roof = 4.52 ± 0.58, and betel box = 4.50 ± 0.51). Also, the assessment from exhibition attendees are in highest ranking (table mirror = 4.87 ± 0.30, Buddhist scriptures and betel box = 4.81 ± 0.40, = 4.81 ± 0.41, lotus flower shaped pedestal = 4.80 ± 0.41, and morable pavilion with pointed roof = 4.79 ± 0.48)